دراسة حسر البصر الوراثي - كردغلي نجوى; رجب محمود; صارم بسام (Latakia University Journal -Medical Sciences Series, 2019)
إن تداخل دور العوامل الوراثية والبيئية في إمراضية الحسر يكشف النقاب عن دور مهم لهذه العوامل وخاصة الوراثية في تطور نماذج الحسر السريرية المختلفة . تمت الدراسة على عينة عشوائية من 30 مريضاً حسيراً بعمر المدرسة 6- 18 سنة أجري لهم دراسة مقارنة مورفولوجية وانكسارية مع آبائهم لتقصي دور العوامل الوراثية والبيئية في إمراضية الحسر . كانت النتائج على النحو التالي : نادراً ما يكون الحسر ولادي , أن يكون أحد الأبوين أو كلاهما حسيراً لايعني أن الأبناء ستكون حسيرة ولكن الفرصة تكون سانحة جداً لتطور الحسر , الحسر البسيط الخفيف ينتج من عوامل متعددة مع تأثير جلي للعوامل البيئية إذ يتطور غالباً نتيجة ضعف المطابقة والاستغراق في مهارات اللغة أي العمل القريب . The interaction between hereditary and environmental factors in the etiology of myopia unravels the role of these factors, especially the hereditary ones, in triggering the development of various types of myopia or short-sightedness. This study is conducted on a random sample of 30 myopic children of schooling age between 6–18. Both childen and parents are evaluated clinically and morphologically to compare and contrast ocular refractive component aimed at investigate hereditary and environmental risk factors in the etiology of myopia. The Results are as follows: congenital myopia is rare, having two myopic parents does not mean that a child will certainly develop myopia; although the chance is much greater, this is not a straightforward inheritance pattern, Simple myopia is the result of several factors, namely environmental ones, and it often develops as a consequence of accommodative insufficiency and spending too much time on language skills such as reading.